(3OQGSGJ aj GdeMGSHI GdeJNUUI (B:s (3MSGHGJ Gdegf GdMQI(B((3ZjQ GdJLGQjI(B)(3, MSGHGJ GdLeYjGJ h GdfhGOj, GdeMGSHI aj TQcGJ Gdfbd GdHMQj, GdeMGSHI aj GdefTBJ GdRQGYjI (B/s - (3gGTe, CMeO YWjIs ((3GdEScfOQjI(B: s (3GdOGQ GdLGeYjI(B, s, 2000)
(3GdeMGSHIaj TQcGJ Gdfbd GdHMQj(B-(3GdeMGSHI aj GdefTBJ GdRQGYjI(B-(3MSGHGJ Gdegf GdMQI(B((3ZjQ GdJLGQjI(B)-(3MSGHGJ GdLeYjGJ hGdfhGOjs
Keywords: (3GdTQcGJ(B-(3eMGSHIs; (3GdeMGSHIs; (3Gdfbd GdHMQjs